La sati indienne au travers de l’histoire. Du suicide héroïque aux martyres du système socio-politique - Harald Tambs-Lyche (Conserveries Mémorielles)
In this article, based on material from Saurashtra (Gujarat) and Rajasthan, I try to trace the history of the sati rite, the suicide of women on the funeral pyre of their husbands. The earliest documented instances of the rite (12th century) appear as individually chosen acts, generally to avenge specific events, which fit into a wider pattern of stories of female heroism. Much later, from the 17th century onwards, the number of satis grows dramatically, until death on the pyre becomes an obligation for all the king’s women – queens, concubines and servants – on the ruler’s death. Clearly, suicide is now imposed on women by the political and religious order. I try to show how this development of sati relates to the diminishing importance of the queen at court, as the ministers and bureaucracy of the early modern state comes to prevail over the earlier importance of marriage alliances for the Royal House.